Bitter Orange (Citrus aurantium L.) Intake Before Submaximal Aerobic Exercise Is Safe for Cardiovascular and Autonomic Systems in Healthy Males: A Randomized Trial - Benjamim, Cicero Jonas R.; Júnior, Francisco Welington de Sousa; Porto, Andrey Alves; Rocha, Élida Mara B.; Santana, Milana D.; Garner, David M.; Valenti, Vitor E.; Bueno Júnior, Carlos Roberto (Frontiers in Nutrition, 2022)
Background: There are still no studies of the cardiovascular safety of the isolated use of C. aurantium in aerobic submaximal exercise. Objective: To evaluate the effect of C. aurantium supplementation on the recovery of cardiorespiratory and autonomic parameters following a session of submaximal aerobic exercise. Methods: Twelve healthy male adults achieved a crossover, randomized, double-blind, and placebo-controlled trial. C. aurantium (600mg, p-synephrine at 30% amount [180mg]) or placebo (600mg of starch) were ingested 90 minutes before evaluation in randomized days. We evaluated systolic blood pressure (SBP), diastolic blood pressure (DBP), pulse pressure (PP), mean arterial pressure (MAP), heart rate (HR) and, HR variability indexes at Rest and during 60 minutes of recovery from exercise. Results: C. aurantium ingestion accelerated the reduction in SBP after exercise, anticipated the return of vagal modulation of the heart after exercise via the HF (ms2), pNN50(%), and 2UV% indices. Moreover, rushed the output of sympathetic modulation after exercise via the 0V% index. No unfavorable cardiovascular effects were achieved for HR, DBP, PP, and MAP parameters. Conclusions: C. aurantium was shown to be safe for the cardiovascular and autonomic systems alongside submaximal aerobic exercise in healthy males.